INFLUENCE OF MARGIN DESIGNS ON FRACTURE RESISTANCE OF ENDODONTICALLY TREATED TEETH RESTORED WITH ENDOCROWNS (Journal of Pharmaceutical Negative Results, 2023)
Aim & objective: The aim of this in vitro study was to study the effectiveness of two different margin designs on fracture resistance of endodontically treated teeth restored with zirconia endocrown restorations.Material method: 20 samples of mandibular first molar was divided into 2 groups (Group B and Group S, n = 10) and endodontically treated followed by margin preparation in order to get endocrowns with 2 mm occlusal thickness fabricated with monolithic zirconia material. Group B represents teeth prepared with butt joint preparation designs. Group S represents teeth prepared with axial reduction & 1 mm shoulder finish line. Fracture resistance was observed for each sample using universal testing machine.Results: Comparative evaluation of fracture resistance after application of Student ‘t’ test between Group S (1114.2 ± 92.81) and Group B (962.8±101.58). shoulder finish line shows better fracture resistance as compared to butt joint. The t value obtained was 3.479 and the p value was found to be significant 0.0022(P<0.05).Conclusion: Preparation design with an axial wall and shoulder finish line of endodontically treated teeth restored with endocrown increases the fracture resistance. However, more studies and researches are needed to ensure the increase of fracture resistance especially considering the conservative preparation designs.